2003
DOI: 10.1002/zaac.200390047
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure and Reactivity of [1, 2‐Bis(diphenylphosphinite)ethane]bromotricarbonylmanganese(I) with Reactions of Phosphites, Phosphonites. and Phosphinites

Abstract: The manganese carbonyl complex [MnBr(CO)3L] (1), where L = Ph2POCH2CH2OPPh2, was prepared by reacting [MnBr(CO)5] with the bidentate ligand 1, 2‐Bis(diphenylphosphinite)ethane. From this compound and the appropriate phosphite, phosphinite or phosphonite ligands were synthesized the complexes [MnBr(CO)2LL′], where L′ = P(OMe)3 (2) or P(OEt)3 (3) and [MnBr(CO)3L′2], where L′ =PPh(OEt)2 (4) or PPh2(OEt) (5).The obtained compounds have been characterized by elemental analysis, mass spectrometry, IR and NMR (1H, 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Besides, the CO ligands trans to Br or Cl are closer to the Mn atom, as expected from the π-donor character of the halogen [e.g. 1.775(4) vs. 1.807(4) and 1.803(4) Å in the chloro-, 1.805 (7) vs. 1.835(6) and 1.841(7) Å in the bromo-complex]. Similarly, the Mn-C bond lengths for the CO ligands trans to oxygen are 1.769 (4) showing that the number of members of the chelating ring involved in this bond is great enough to induce no significant steric hindrance in the bidentate phosphane ligand.…”
Section: Synthesis Of the Complexesmentioning
confidence: 94%
See 2 more Smart Citations
“…Besides, the CO ligands trans to Br or Cl are closer to the Mn atom, as expected from the π-donor character of the halogen [e.g. 1.775(4) vs. 1.807(4) and 1.803(4) Å in the chloro-, 1.805 (7) vs. 1.835(6) and 1.841(7) Å in the bromo-complex]. Similarly, the Mn-C bond lengths for the CO ligands trans to oxygen are 1.769 (4) showing that the number of members of the chelating ring involved in this bond is great enough to induce no significant steric hindrance in the bidentate phosphane ligand.…”
Section: Synthesis Of the Complexesmentioning
confidence: 94%
“…Deuterated solvent (CDCl 3 Merck) for NMR measurements was dried over molecular sieves. 1,2-Bis(diphenylphosphinoxy)ethane and 1,2 bis(diisopropylphosphinoxy)ethane were prepared as described previously [9], [MnBr(CO) 5 ] was obtained from [Mn 2 (CO) 10 ] by the method described in literature [10] and the starting product [MnBr(CO) 3 L 1 ] has been previously reported [7]. AgSO 3 CF 3 , AgCO 2 CF 3 (Aldrich), CH 3 CN, KCN and KSCN (Merck) were used as supplied.…”
Section: Materials and Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the free phosphites, the latter were not detectably coupled to phosphorus. Other researchers have noted both broad singlets and resolved doublets for the POCH 2 CH 2 signals of phosphite complexes [30]. The 13 C NMR spectra also showed a single peak for the CO ligands (212.2-213.0 ppm), in two cases with resolved phosphorus coupling ( 2 J CP = 39.8-39.5 Hz).…”
Section: New Results: Extension To Phosphite Ligandsmentioning
confidence: 92%
“…A similar situation occurs with the signals corresponding to the methylene groups of the bidentate ligand. As observed in other halide compounds bearing this ligand, [11] these groups usually display one multiplet for each proton. In our case different multiplets were observed that integrate as one proton each and these coexist with other signals of lower intensity that may correspond to the cisoid structure.…”
Section: Reaction Of Compound 1 With L -Preparation Of [Ru 2 (µ-Cl) 3mentioning
confidence: 94%